Solve this equation using the quadratic formula.

3x² + 5x - 3 = 0

3x² + 5x - 3 = 0

-b ± √(b² - 4ac)

--------------------- = x {the quadratic formula}

2a

a = 3, b = 5, c = -3

-5 ± √[5² - 4(3)(-3)]

-------------------------- = x {substituted into quadratic formula}

2(3)

-5 ± √(25 + 36)

----------------------- = x {simplified under square root sign and on bottom}

6

-5 ± √61

------------ = x {added 25 and 36}

6

-5 ± 7.81

------------- ≈ x {evaluated square root of 61 and rounded}

6

≈ (-5 + 7.81)/6 or (-5 - 7.81)/6 {split using the ± sign}

≈ 2.81/6 or -12.81/6 {simplified}

**x ≈ .47 or -2.14**{divided}

*© Algebra House*